Improving Postsurgical Management of Rhinoplasty: A Comprehensive Review of Existing Literature - Villarroel, Pedro P.; Langdon, Cristobal; Arancibia-Tagle, Diego (Facial Plastic Surgery, 2025)
Rhinoseptoplasty addresses both nasal deformities and functional issues. Effective postoperative care is essential for optimal recovery, as complications such as swelling, bruising, and pain can adversely affect healing and patient satisfaction. Proper postoperative care emphasizes the significance of comprehensive management strategies.A systematic literature review was performed utilizing the PubMed and Cochrane databases to identify articles published between 2014 and 2024 that specifically addressed postoperative care following rhinoplasty. Of 191 articles, 22 met the preestablished inclusion criteria. We assessed the quality of evidence according to the Oxford Centre for Evidence-Based Medicine's Levels of Evidence.Seven key studies were analyzed, exploring a range of postoperative care interventions, including administering corticosteroids, elevating the head during and after the procedure, using alternative therapeutic approaches, and applying cooling techniques.Postsurgical recovery after rhinoplasty involves managing pain, swelling, and bruising, among other complications. Educating patients about expected outcomes and the healing process helps alleviate their anxiety and uncertainty. Corticosteroids have proven effective in controlling swelling and bruising. Antibiotics are generally not recommended. Silicone septal splints provide support, particularly when stabilization of an injured mucous membrane or septal cartilage is required; however, nasal packing is not recommended. Adhesive strips can help reduce edema in the dorsal and supratip areas. Positioning patients in a 20° reverse Trendelenburg position during surgery, followed by maintaining the head elevated at a 90° angle postoperatively, has significantly reduced edema and ecchymosis. Using a cannula for drainage and cooling techniques has been shown to reduce postoperative morbidity effectively.Rhinoplasty is a common facial plastic surgery, yet there is no consensus on optimal postoperative care. Key strategies include silicone splints, subperiosteal drainage, nasal taping, cooling, corticosteroids, and intra- and postoperative head elevation. However, further systematic trials are necessary to refine these strategies and improve patient outcomes.
Keywords: rhinoplasty postoperative care; postsurgical care in rhinoplasty; postoperative management rhinoplasty; periorbital edema reduction rhinoplasty